Euphemisms and teacher–student interactions - Bloch-Rozmej, Anna (LingBaW. Linguistics Beyond and Within, 2023)
The quality of teacher-student interactions appears to be one of the most significant prerequisites for effective instruction. One of the factors involved in determining this quality is definitely teacher talk that should adequately correspond both to the type of knowledge the teacher intends to transfer and students’ ability to absorb this knowledge. The latter we claim is directly related to the students’ attitude to the subject itself and the teacher. In this article we will delve into the problem of euphemisms as part of teacher and student talk with a view to determining the extent to which they might affect teacher-student interactions. The issue of euphemism use and their role in building positive relations in the language classroom will be discussed from the perspective of teachers’ experiences. To this end, we chose the research tool of an online questionnaire addressed at university teachers. The survey was administered in June 2023 and the results will be described and analyzed in the forthcoming pages. Euphemism use will also be considered as a manifestation of language creativity that should characterize good language teachers.